Between pen and pixel : comics, materiality, and the book of the future - Kashtan, Aaron (Studies in comics and cartoons., 2018)
"Through case studies of the work of Alison Bechdel, Matt Kindt, Lynda Barry, Carla Speed McNeil, Chris Ware, and Randall Munroe, this monograph argues that paying attention to comics helps us understand the future of the book"--